1996
DOI: 10.1172/jci119009
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin stimulates NF-kappaB activation and interleukin 1beta gene expression in cultured human fibroblasts.

Abstract: Bradykinin (BK), a pluripotent nonameric peptide, is known for its proinflammatory functions in both tissue injury and allergic inflammation of the airway mucosa and submucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 41 publications
7
84
0
Order By: Relevance
“…Our results extend this function to the activation of a transcription factor, suggesting that other G proteins may also activate NF-B through PLC␤. Indeed, several GPCRs that primarily couple to G␣ q have been shown to stimulate NF-B activation (27,49,50). We have shown that all three PLC␤ isoforms found in non-neuronal cells can function in this capacity.…”
Section: Discussionmentioning
confidence: 77%
“…Our results extend this function to the activation of a transcription factor, suggesting that other G proteins may also activate NF-B through PLC␤. Indeed, several GPCRs that primarily couple to G␣ q have been shown to stimulate NF-B activation (27,49,50). We have shown that all three PLC␤ isoforms found in non-neuronal cells can function in this capacity.…”
Section: Discussionmentioning
confidence: 77%
“…Nuclear extracts were prepared by a modified method of Dignam et al (24) and EMSA were performed as previously described (25). Oligonucleotides and their complementary strands for EMSAs were from Promega.…”
Section: Emsamentioning
confidence: 99%
“…Several G protein-couple receptors, including the B2 BK receptor, have been shown to mediate NF-B activation and cytokine gene transcription in human epithelial cells and fibroblasts (16,17). BK-stimulated NF-B activation has been demonstrated to be mediated through B2 BK receptors coupled to the G i /G o class of heterotrimeric G proteins (16).…”
mentioning
confidence: 99%
“…BK-stimulated NF-B activation has been demonstrated to be mediated through B2 BK receptors coupled to the G i /G o class of heterotrimeric G proteins (16). Activation of the small GTP-binding protein, Rho A, and PI3K are involved in BK-stimulated NF-B activation in A549 cells (17,18).…”
mentioning
confidence: 99%